Optimizing anther culture for barley breeding - O. MANNINEN (Agricultural and Food Science, 2008)
Barley anther culture methods were optimized for the production of doubled haploid lines from Finnish spring barley (Hordeum vulgare) breeding material. 22 F 1 -progenies of two-rowed barley cultivars ('Bonus', 'Inari', Jo1610, 'Kustaa', 'Kymppi', 'Prisma') and six-rowed barley cultivars ('Arve', 'Botnia', 'Larker Mutant', OB264, 'Rolfi', WW7860) were used for the experiments. The effect of basic induction media, pretreatment on mannitol medium, density of anthers, incubation temperature and light regime were tested. Pretreatment of anthers for 4 days on medium containing 0.175 M mannitol was beneficial for all 8 genotypes tested and increased production of green plants per 100 anthers from 26% to 74% for the best genotype ('Inari' x 'Kymppi' F 1 ). A lower anther density (1.6 anthers per cm 2 ) was better than a more dense one. A modified MS-medium with ammonium nitrate partly replaced with glutamine (MMS-MG) was slightly better than a medium based on N 6 salts (N 6 -MG), and addition of 100 mM silver nitrate reduced both plant and green plant production. No significant differences were observed between the effects of incubation temperatures (20°C vs. 25°C) or the light regime (darkness vs. weak light) during incubation of anthers. In each experiment the genotypic effect was prominent and the recalcitrance of some genotypes was apparent. Green plants were produced however from all genotypes.;